Обгрунтування застосування світлодіодного освітлення в птахівничих приміщеннях - Червінський, Л. С.; Книжка, Т. С.; Романенко, О. І. (Енергетика і автоматика, 2017)
THE SUBSTANTIATION OF APPLICATION OF LED LIGHTING IN POULTRY PREMISESL. Chervinsky, T. Knizhka, A. Romanenko Topicality. It is known that optical radiation, as a factor in the environment, has a great influence on the growth, development and viability of the bird. Under the influence of light in the blood, the number of erythrocytes, hemoglobin, calcium and phosphorus increases, nitrogen exchange increases, and the nitrogen balance becomes positive.Analysis of recent research and publications. V Larionov, V. Pood, S. Fox, D. King. and other researchers have proven that optical radiation in the body of the bird causes profound physiological changes, especially in the endocrine and generative systems. The light energy perceived by the retina is transformed into nerve impulses that, stimulating the corresponding nerve centers, increase the vital tone of the body, namely metabolism, thus stimulating the general physiological and reproductive function of the bird.The purpose of the study is to investigate the spectral composition of light sources and their impact on productive poultry quality.Materials and methods of research. In the process of research, methods of photometry, mathematical modeling and system analysis were used.Results of the research and their discussion. Light (visible radiation) can have a thermal, chemical and electrical effect on the body of the bird. In this case, the light rays are absorbed by various tissues of the body, where their energy is converted into thermal, electrical, chemical, and electromagnetic waves, acting on the surface of the body, carry out a resonance effect, which is called radiation or radiation.The department of electric and electrotechnology of NUBiP of Ukraine conducted research and analyzed the spectral characteristics of modern lamps, which are used for illumination of laying hens. These are OSRAM DULUX S 9W / 830, OSRAM DULUX S / E 11W / 840, and OVOSTAR M / N: PV-4ft-14W LED Tube and LedLife LFPL 600-22.5.Investigation of spectral characteristics was carried out using the monochromatic block of the spectrophotometer SF4. The radiation of the light-emitting part of a particular lamp was directed to the perceptive crack of the monochromator. The expanded radiation spectrum through the output chip of the monochromator was measured by a Sensor of a sensory digital luxmetre of the type MS6610.The research was conducted in three groups. In order to preserve the given light regime in the 1st group, incandescent lamps were used, in the 2nd - fluorescent lamps, in the 3rd - LED lamps. The duration of light day and the intensity of irradiation on the working surface were the same. The studies were conducted within three months. The results of the studies are presented in the table.Conclusions and perspectives. Studies have shown that fluorescent lamps and, in particular, LED lighting contributes to the fastest reach of 50% and 75% of carrying capacity, as well as the bursting peak, which occurred at 8 and 11 days earlier than when lit by incandescent lamps. It has been established that the use of fluorescent lamps and LED lamps results in an increase in the intensity of carrier chickens by 3.3% and 7%, which confirms the greater promise of using LED lamps over luminescent lamps to maintain room for laying hens.